The First Woman Philosopher with a Doctorate: Elena Cornaro Piscopia - Kalnická, Zdeňka (Studia z Historii Filozofii, 2021)
The study analyses the circumstances under which Elena Cornaro Piscopia became the first woman in the world to earn a Doctor degree in Philosophy, which she received from the University of Padua in 1678. The author presents the broader context of the outstanding accomplishment. She points out that, although universities did not allow women to enrol to study, Elena Cornaro managed to earn a doctorate thanks to several favourable circumstances. Of these, the author emphasises the tradition of intellectual centres at Renaissance courts in Italy, which were led by educated women-aristocrats; the development of the Venetian Republic in the sixteenth and seventeenth centuries, which affected the position of women, particularly those from aristocratic families; the openness of universities, namely the Universities of Padua and Bologna. Special attention is given to the family background, life, and studies of Elena Cornaro. The final part of the paper deals with other women philosophers of the seventeenth and eighteenth centuries.